Comparative Analysis of Growth Rate Enhancement and Ge Redistribution during Silicon-Germanium Oxidation by Rapid Thermal Oxidation. (18th August 2016) - Rozé, Fabien; Gourhant, Olivier; Blanquet, Elisabeth; Bertin, François; Juhel, Marc; Abbate, Francesco; Pribat, Clement; Duru, Romain
Abstract : SiGe-On-Insulator layers are promising materials for high mobility pMOSFET channels and can be fabricated by the condensation technique. This technique is based on SiGe oxidation and a sound understanding of it is thus needed in order to fabricate optimized SGOI structures. The present study is a read-across of oxidation kinetics and Ge redistribution during dry Rapid Thermal Oxidation (RTO) of SiGe layers with different compositions and different oxidation temperatures. The evolution of the Ge concentration below the oxidation front is found to follow different regimes depending on the oxidation temperature. We examine them in light of a competition between oxidation rate and diffusion rate. It is also shown that RTO of SiGe is faster than Si and that the oxidation rate depends not only on the initial Ge concentration, but also on the oxidation temperature. A correlation between the Ge concentration below the oxidation front and oxidation kinetics is evidenced.